Air quality simulation over South Asia using Hemispheric Transport of Air Pollution version-2 (HTAP-v2) emission inventory and Model for Ozone and Related chemical Tracers (MOZART-4). (December 2015) - Surendran, Divya E.; Ghude, Sachin D.; Beig, G.; Emmons, L.K.; Jena, Chinmay; Kumar, Rajesh; Pfister, G.G.; Chate, D.M.
Abstract: This study presents the distribution of tropospheric ozone and related species for South Asia using the Model for Ozone and Related chemical Tracers (MOZART-4) and Hemispheric Transport of Air Pollution version-2 (HTAP-v2) emission inventory. The model present-day simulated ozone (O3 ), carbon monoxide (CO) and nitrogen dioxide (NO2 ) are evaluated against surface-based, balloon-borne and satellite-based (MOPITT and OMI) observations. The model systematically overestimates surface O3 mixing ratios (range of mean bias about: 1–30 ppbv) at different ground-based measurement sites in India. Comparison between simulated and observed vertical profiles of ozone shows a positive bias from the surface up to 600 hPa and a negative bias above 600 hPa. The simulated seasonal variation in surface CO mixing ratio is consistent with the surface observations, but has a negative bias of about 50–200 ppb which can be attributed to a large part to the coarse model resolution. In contrast to the surface evaluation, the model shows a positive bias of about 15–20 × 10 17  molecules/cm 2 over South Asia when compared to satellite derived CO columns from the MOPITT instrument. The model also overestimates OMI retrieved tropospheric column NO2 abundance by about 100–250 × 10 13  molecules/cm 2 . A response to 20% reduction in all anthropogenic emissions over South Asia shows a decrease in the anuual mean O3 mixing ratios by about 3–12 ppb, CO by about 10–80 ppb and NOX by about 3–6 ppb at the surface level. During summer monsoon, O3 mixing ratios at 200 hPa show a decrease of about 6–12 ppb over South Asia and about 1–4 ppb over the remote northern hemispheric western Pacific region. Highlights: Simulations of trace gases over South Asia using MOZART-4 and HTAP-v2 emissions. Evaluated the model results with satellite and ground based observations. Long range transport of pollution from South Asia during summer monsoon season.